Numpy Library Capabilities. Vectorized Calculation In Numpy Va Type Of Information - Assistent Salimov Jamshid Obid o’g’li; Assistent Abror Mamaraimov Kamalidin o'g'li; Assistent Normatov Nizomiddin Kamoliddin o‘g’li (Genius Journals, 2022)
The article shows the difference between vectorized and conventional in the NumPy library and clearly defining the type of data when creating data. In addition, other types of information are considered.
Keywords: vectorized; dtype; tools; default